Heat Integration Analysis for Enhancing Energy Efficiency in the Pre-Design Phase of a Sodium Hydroxide Factory Using Pinch Technology - Salwa Shofiyya Hayya; Annisa Puspitasari; Kenes Cahyaningrum; Maura Nur Aulia (Journal of Vocational Studies on Applied Research, 2025)
Energy efficiency plays a crucial role in the initial design of chemical plants, as it directly influences operational costs and process sustainability. In sodium hydroxide plants, the substantial thermal energy demand, especially in heating and cooling units, necessitates effective energy optimization strategies. This study seeks to enhance energy efficiency in the preliminary design of a sodium hydroxide plant by incorporating heat exchangers (HE) through a Heat Exchanger Network (HEN) approach, utilizing the HINT application based on the Pinch Analysis method. Process stream data, including temperature, mass flow rate, and heat capacity flow rates of hot and cold streams, were analyzed to identify the pinch point, minimum heating and cooling utility requirements, and the optimal heat exchanger network configuration. The findings reveal that adding heat exchangers significantly boosts internal heat recovery and reduces the need for external utilities. Consequently, applying Pinch Analysis with the HINT application at the preliminary design stage of a sodium hydroxide plant effectively enhances energy efficiency, supporting a more economical and sustainable plant design.